A Thematic Review of the Role of Positive Teacher-Student Relationships in English Classroom Management Success - Nabiha Mohammed Nazmul Huda MD Nazrul Islam; Noor-A-Robiyat Binta Ahammad (Yayasan Visi Intan Permata, 2025)
Effective English classroom management has long been a crucial component of successful teaching and learning. Relational techniques have been increasingly emphasized in teaching research over the past few decades. Positive relationships between teachers and students are essential for creating classrooms that are well-run and productive. This thematic synthesis draws on 50 peer-reviewed articles from 2010 to 2024 to demonstrate how professional learning, communication, empathy, emotional connection, and an inclusive approach can collectively have a positive impact on classroom management across various educational settings. To identify recurring themes and patterns in the emotional, cultural, communicative, and instructional contexts of teacher-student relationships, a qualitative thematic analysis was employed. According to research, relational communication, cultural awareness, emotional intelligence, and respect for one another significantly enhance academic performance and student engagement, while also reducing behavioral issues. Furthermore, it has been found that organized teacher training in relational and emotional intelligence plays a crucial role in advancing sustainable management techniques. Effective classroom environments are built on a basis of positive, compassionate, and inclusive teacher-student relationships, according to the review's findings. It follows that to create emotionally secure and engaging learning environments for all students, teachers and policymakers should integrate relational capacities into professional development and support.